Time Pressure and Teams: Contextual Factors Influencing Task Experience when Using a Cognitive Aid. (September 2018) - Hicks, W. Braxton; Pryor, Mak; Sprufera, John; Greene, Amy; Byrne, Vicky; McLaughlin, Anne Collins
Guidelines are needed to help designers create cutting-edge cognitive aids for complex procedures, particularly when those aids support non-expert operators. To create guidelines, the factors that might interact with the aid design need be explored with non-experts, such as time pressure and the number of operators. We manipulated time pressure and number of team members in setting up a medical ventilator while using a cognitive aid. We measured dependence on the aid, performance, subjective workload, and team dynamics to better understand their influence on the use of a cognitive aid to accomplish a complex task by non-expert operators. Individuals reported a significantly higher mental workload level than teams and those under time pressure reported higher temporal workload. These data can contribute to design guidelines.